Perencanaan Sistem Persampahan Al-Amin Living Lab Dan Industrial Park - Fitri, Rahmadhani; Sigit, Faurantia Faurlana; Iskandar, Benny; Rahmadani, Andini (Universitas Medan Area, 2024)
The population growth rate, aligned with the increasing diverse needs, will raise the amount of waste/residue or refuse, both from consumption processes and activities carried out, in the form of trash. The purpose of this research is to understand the waste management system planning of Al-Amin Living Lab and Industrial Park. The research material is the site located in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, considering and paying attention to the existing waste management system. Waste that is improperly disposed of will impact the surrounding community's activities, potentially leading to diseases. The data used in this study involved several data collection techniques, including field observations and document analysis, conducting direct observations in the field to examine waste management practices such as collection, sorting, transportation, and disposal. Based on the research results, it is explained that, in general, the planning activities for waste management in the Al-Amin Living Lab and Industrial Park area include containerization, collection, transfer, and transportation of waste to the landfill (TPA). In terms of waste management planning in the Al-Amin Living Lab and Industrial Park area, it will consider the needs of people, the amount of waste generated, containerization, and the Temporary Waste Storage (TPST) of the Al-Amin Living Lab and Industrial Park, as well as effective waste management.